Assessment of indicators of fecal contamination in soils treated with biosolids for growing grasses - Campos, Maria Claudia; Professor (2015)
Developing countries currently face challenges related to the management and disposal of biosolids that result from wastewater treatment. One of the most important issues they must deal with involves the maximum level of pathogens permitted and the effect they may have on the environment and human health once they are used for agricultural purposes. In order to learn about the risk generated by these kinds of practices, we assessed the behavior of indicators of fecal contamination in grasses used to feed dairy cattle. The study area was divided into two plots: an experimental plot in which diluted biosolids were applied and a control plot without the application of biosolids. We collected samples from soil, grass, surface water and groundwater and analyzed the presence of fecal coliforms, Salmonella spp., somatic phages and helminth eggs. Experimental and control plots showed a decrease in the concentration of bacterial indicators assessed in soil, and low concentrations in surface water, groundwater and grass. Concentrations of viral and parasite indicators tend to decrease more slowly. Our results show that this way of biosolid management allows a better use of its benefits as an organic amendment by lowering the sanitary risk due to the presence of pathogens.